The serum-inducible mouse gene Krox-24 encodes a sequence-specific transcriptional activator. - Lemaire, P (1990)
The mouse gene Krox-24 is transiently activated during cell cycle reentry. It encodes a protein with three zinc fingers similar to those of the transcription factor Sp1. Here we present a biochemical characterization of the gene products. Krox-24 mRNA is translated into two proteins of 82 and 88 kilodaltons, designated p82Krox-24 and p88Krox-24, respectively. p82Krox-24 is initiated at the first AUG codon of the open reading frame, whereas synthesis of p88Krox-24 starts at a non-AUG codon located upstream. Both proteins were synthesized in HeLa cells infected with recombinant vaccinia viruses expressing Krox-24 cDNAs. Under these conditions, they were found phosphorylated on serine residues and glycosylated. The availability of the proteins made possible the determination of the DNA recognition sequence. In vitro, Krox-24 bound specifically to the sequence 5'-GCG(C/G)GGGCG-3'. This sequence is similar but not identical to the Sp1 target sequence. Insertion of an oligomer for the binding site in cis, close to the herpes simplex virus thymidine kinase promoter, rendered this promoter responsive to Krox-24. Krox-24 is therefore a sequence-specific transcriptional activator. Krox-24-binding sites were found upstream of several serum-inducible genes, raising the possibility that Krox-24 is involved in the regulation of these genes.